Pemanfaatan Limbah Ampas Kelapa sebagai Media Kolase untuk menstimulasi Keterampilan Motorik Halus Anak di RA Hasanah - Wahyuni, Sri; Zahriani Jf, Nurul (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to describe the implementation of collage activities using coconut pulp as a learning medium to stimulate fine motor skills of early childhood students at RA Hasanah. The background of the research is the need for learning media that are inexpensive, easily obtained, environmentally friendly, and contextual. The study employed a qualitative descriptive approach with primary data collected through observation and documentation, and secondary data obtained from relevant literature. Data analysis followed the Miles, Huberman, and Saldana model, with data validity ensured through triangulation. The findings indicate that the use of coconut pulp in collage activities improved six indicators of fine motor skills, namely gripping and holding tools, finger-hand coordination, finger muscle strength, movement accuracy, task completion speed, and independence. Children were more focused and enthusiastic, producing neat and efficient works. Moreover, the activity positively affected socio-emotional aspects such as cooperation, appreciation of peers’ work, and self-confidence. The study recommends that early childhood teachers utilise environmentally friendly waste as creative media to train fine motor skills while instilling environmental awareness from an early age skills but also integrates environmental awareness values from an early age.